“The End of History of Art” in the Theory of A. Danto - Vabalaitė, Rūta Marija (Problemos, 1996)
The article deals with Arthur C. Danto’s theory of the end of art. It presents an analysis of his definition of art and discusses the models of the development of art. The linear or progressive model of the history of art might be generally presented in terms of an imperative to replace inference to perceptual reality with something equivalent to what perceptual reality itself would present. This model is not consistent with the development of all branches of art, and it is not applicable if art is interpreted as expression. Art, seeing its task to be primarily that of providing an account, of its essence which began to seem to be defined by providing just such an account, reveals the possibility of conceiving it as having a kind of progressive cognitive history. Danto defines it in terms of Hegelian art history. He supposes that self-consciousness is what aims at, so that art executes its historical mission by, at last, becoming philosophy. The main problems of such a theory are the same as that of the Hegelian system of philosophy.